Osobni i kolektivni identiteti : napomene o ulozi pojma u suvremenoj teoriji - Šesnić, Jelena (Array, 2007)
In the first part of her article entitled “ Individual and Collective Identities: Some Remarks on the Concept and Its Status in Contemporary Theory” , Šesnić highlights the concept of identity and its acquisition by way of variegated processes of identification. She pays special attention to its application in more specific contexts, that come about by collocations of individual, national, ethnic, subaltern, postcolonial and gender modifiers. Pertinent to the overall argument is her analysis of the vicissitudes of national and ethnic identities provided by the examples of the Irish rock-band U2 and Toni Morrison’ s novel Beloved. U2 can be seen as an instance of an identity shift brought about by specific socio-economic factors— the pressure of the global and neo-liberal market and cultural practices. In the band’ s early phase, contends the author, it had a strong impact on the emergence and shaping of an Irish masculine identity playing upon the stereotypes of “ Irishness” , Catholicism and masculinity. However, even though the band “ has always remained sensitive to social issues and has even become politically engaged in the war in Bosnia..., human rights issues, the Western policies towards African countries, etc.” , its initially powerful national charge, especially persistent in its early period, has subsequently become blurred by international and global trends. In such a way, the band’ s trajectory becomes illustrative of the flexibility of the concept of identity, regardless of how predetermined and preordained it may seem in its local and traditional guise, and shows how it can be modified under the influence of the global and neo-liberal tendencies especially promoted by the global music industry. Šesnić's other analysis concerns itself with the question of identity tentatively explicable on the basis of the ruptured genealogy and intermittent connections among personal, collective and historical memory, and their role in the constitution of ethnic and national histories. It is interesting to point out that in the text the author mentions different uses of “ national” and “ ethnic” in the US and the European contexts, respectively. Toni Morrison’ s novel Beloved (1987) nowadays occupies a privileged space in the American literary canon. Šesnić cites the concept of re-memory, as seen in the novel, to show how the models of familial, blood and kinship ties are transmitted through the female line thus enabling the process of collective memory, which, according to Ricoeur, works as a “ living memory” uncontained by historiographic disciplining. Furthermore, out of Beloved’ s ontological impossibility to embody, anchor and become a witness for the unutterable trauma of the Afro-American community in the New World, the author strives to create new strategies to allow the recognition and witnessing of this incipiently founding experience. In other words, re-memory and individual memory should expand into a collective enterprise. History, for the black community, “ is not merely an academic exercise but is constituted in the process of memory. ... The mechanism at work is in fact supposed continuously to transpose and transmute memory into history, before the former is caught up in a wilful or inescapable amnesia” . For Morrison, as pointed out by Šesnić, the critical question is “ how to represent a possibility for generations in the black community ... to begin to ‘ re-member’ that which Beloved portends— an experience which they could not possess but such that is foundational for the community” , based as it is on remembering the past as history. This is something that should be done, contends the author, before forgetting becomes a key factor in the emergence of a nation (Ernest Renan).